Genotypes, haplotypes and diplotypes of three XPC polymorphisms in urinary-bladder cancer patients - Verdier, Petra J. de; Sanyal, Somali; Lorenzo Bermejo, Justo; Steineck, Gunnar; Hemminki, Kari; Kumar, Rajiv (Mutation research. Fundamental and molecular mechanisms of mutagenesis, 2010)
PURPOSE: The XPC gene is involved in DNA damage recognition in the nucleotide excision repair pathway (NER). We investigated the additive effects of single nucleotide polymorphisms (SNPs) in bladder-cancer patients and population controls for three XPC polymorphisms: A499V (C>T), K939Q (A>C), and poly AT (PAT, -/+). - EXPERIMENTAL DESIGN: 311 bladder-cancer patients from a population-based cohort and 337 population controls were genotyped using the PCR-restriction fragment length polymorphism (RFLP) technique. - RESULTS: We found complete linkage between the K939Q (A>C) and PAT (-/+) polymorphisms and therefore only the K939Q (A>C) polymorphism was included in analyses. The over all estimated odds ratio was 1.7 (95% CI 1.3-2.4) for A499V (C>T) and 1.4 (95% CI 1.0-2.0) for K939Q (A>C). The associated odds ratio increase with the variant allele homozygotes was six-fold for the A499V (C>T) and three-fold for the K939Q (A>C) polymorphism (OR=5.7, 95% CI 3.4-9.5 and OR=2.6, 95% CI 1.3-5.6, respectively). The variant allele haplotype of the two polymorphisms (T₄₉₉C₉₃₉) was associated with a nearly four fold increased odds ratio compared to the common allele haplotype (C₄₉₉A₉₃₉) (OR=3.6, 95% CI:1.9-6.9). Combined genotype analysis showed an increased disease association with increasing number of variant alleles (p<0.0001), with a dominant effect of the A499V polymorphism. In addition we observed association of the disease with increasing number of variant alleles for the A499V polymorphism and an early age at diagnosis (p=0.004). - CONCLUSIONS: Our results suggest an association between the XPC genotypes of the A499V, K939Q and PAT polymorphisms and urinary-bladder cancer. We propose a poly-allelic effect of these polymorphisms where the cumulative effect on disease becomes higher than the individual allelic effects.